Growth and mineral nutrition of field crops - Fageria, N. K. , 1942-; Baligar, Virupax C.; Jones, C. Allan (Books in soils, plants, and the environment, 2011)
"This new edition of a bestseller examines plant nutrition's role as one of the most important limiting factors that must be overcome to optimize food production.Extensively revised and update, the edition provides comprehensive coverage of on topice such as genetics, physiological and agronomic bases of crop growth.It covers soil-plant-climatic relationship that govern the growth and mineral nutrition of crops in temperature and tropical region. The book contains two new chapters covering remediation of heavy metal contaminated soils and cover crops as well as several new figures, references, and tables"